Where Do We Go from Here? - Peterson, Gregory R. (Zygon, 1999)
Beginning with the End represents an excellent collection of articles devoted to the thought of Wolfhart Pannenberg. This volume includes many of the most important thinkers in the science-religion dialogue and shows as well the importance and impact of Pannenberg's theology. This response addresses themes that surface in several of the articles: What is religion? What is science? What is theology? What is God? On some of these themes there is agreement, on others sharp disagreement. The conclusion also considers what this volume suggests about the future of Pannenberg's theology.